The infl uence of new religious movements on modern religious situation in Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
The infl uence of new religious movements on modern religious situation in Kazakhstan on the whole as wellas its infl uence on the ethno-confessional mentality, extremalization of conscience and behavior of Kazakhstancitizens is examined in the present article.Key words: new religious movements, extremism, ethnoconfessional identifi cation.